War Museums in Postwar Lebanon: Memory, Violence, and Performance. Issue 1 (2nd January 2019) - Larkin, Craig; Parry-Davies, Ella
Abstract: This article examines three museums that address Lebanon's history of conflict: the newly opened Beit Beirut on the capital's former Green Line, the Hezbollah-run Mleeta Resistance Tourist Landmark in south Lebanon, and Umam Documentation and Research's online archive "Memory at Work." Each testing the parameters of what the term museum can mean in Lebanon today, these cases highlight the still-contested nature of war narratives. While many Lebanese youth express desire for a shared national history of the civil war, the affective complexities of recuperated memorial sites and the inconsistent involvement of the state suggest that the possibility of publicly staging such a history is far from secure.